THE INFLUENCE OF USING KIT OF SCIENCE FOR KIDS TO ELEMENTARY SCHOOL STUDENTS’ CONCEPT MASTERY - Yosi Gumala; Nunuy Nurkaeti; Sani Aryanto; Ernawulan Syaodih; Achmad Samsudin (IKIP Siliwangi, 2020)
This research was conducted to determine the increase in concept mastery of primary school students' teaching material through the use of media kits of science for kids. The research method used was quasi-experimental research using the matching only pretest and posttest control group design. The learning process uses the media kit of science for kids and the traditional learning media is used as a comparison. Learning takes place during four meetings, each learning process is carried out observing the implementation of learning activities. Research subjects were 55 students consisting of 28 students using the media kit of science for kids and 27 students with traditional learning media. The research instrument uses multiple choice tests for concept mastery. The data analysis technique used n-gain mean data and non-parametric test t test. The value of n-gain in class with kit of science for kids media is 0.47 while in class with traditional learning media is 0.26. The results showed that increased understanding of the material using the kit of science for kids was higher than students who received traditional learning media.